OPTIMASI KONSENTRASI ETHYLENE GLYCOL FLUIDA KERJA PADA PERANCANGAN PARABOLIC TROUGH CONCENTRATOR DENGAN REPLEKTOR - Jati Widiputra; Iskendar Iskendar; Reza Abdu Rahman (Magister Teknik Mesin Universitas Pancasila, 2020)
An excellence innovation for reducing greenhouse gases are done by developing a new water heater model for household applications. The application of the new model water heater by utilizing Parabolic Trough Concentrator with an indirect heating system uses heat transfer fluid able to improve the reliability of water heater compared to the thermosyphon model. Optimization for the new model is done by enhancing the reflector material and also heat transfer fluid. The experiment is done by applying the same standard measurement in order to set an adequate data for each model. The optimal reflector for the system to concentrating the solar power is polymer substrate as the fluid heated faster. The water-based solution with ethylene glycol 50:50 (v/v) for heat transfer fluid shows the best performance by achieving 98,2 oC for the 10th minute, and after one hour, the final temperature is 100,5 oC. By using a polymer substrate as a reflector for the Parabolic Trough Concentrator and using heat transfer fluid based on ethylene glycol water-based solution by concentrator 50:50 (v/v) shows the best performance among all sample with the fastest heating rate and the highest final temperature after the one-hour experiment. It shows this model has advantages to improve the system reliability by increasing the heating rate of the heat transfer fluid, which able to heat the water on the system faster.